The Evolution and Dissemination of Methicillin Resistance Determinant in Staphylococcus aureus - Suhaili, Ts. Dr. Zarizal (InTechOpen, 2017)
Staphylococcus aureus is an opportunistic pathogen and is frequently associated with the antimicrobial resistance. There has been horizontal gene transfer of Staphylococcus chromosome cassette mec (SCCmec) among the staphylococcal species that colonize a similar colonization niche, which eventually results in emergence of new variant with enhanced survival ability in terms of antimicrobial resistance and virulence level in S. aureus. Evolution and dissemination of SCCmec structure resulted in the emergence of methicillin-resistant S. aureus (MRSA) clones around the world covering hospital, community, and livestock settingsǯ MRSA also has the ability to resist different antibiotic profiles known as multidrug-resistant S. aureus (MDR S. aureus).